Red mud and li-ion batteries: a magnetic connection - Suryawanshi, Anil; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra B. (Chemsuschem, 2016)
Exceptional Li-ion battery performance is presented with the oxide component of the anode was extracted from red mud by simple magnetic separation and applied directly without any further processing. The extracted material has -Fe2O3 as the major phase with inter-dispersed phases of Ti, Al, and Si oxides. In a half-cell assembly, the phase displayed a reversible capacity (approximate to 697mAhg(-1)) with excellent stability upon cycling. Interestingly, the stability is rendered by the multiphase constitution of the material with the presence of other electrochemically inactive metal oxides, such as Al2O3, SiO2, and Fe2TiO4, which could accommodate the strain and facilitate release during the charge-discharge processes in the electrochemically active maghemite component. We fabricated the full-cell assembly with eco-friendly cathode LiMn2O4 by adjusting the mass loading. Prior to full-cell assembly, an electrochemical pre-lithiation was enforced to overcome the irreversible capacity loss obtained from the anode. The full-cell delivered a capacity of approximate to 100mAhg(-1) (based on cathode loading) with capacity retention of approximate to 61% after 2000cycles under ambient conditions.